Proceedings of the 2013 International Conference on Advanced ICT 2013
DOI: 10.2991/icaicte.2013.145
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining Approach for Making Prediction of Students Success

Abstract: Although data mining represents the computational method of data processing, its use in education is still relatively new, i.e. its use is intended for discovering implicit, previously unknown, and useful knowledge out of existing data with an aim to make quality decisions in function of improvement of education system. The study was conducted by surveying the population of high school students in Tuzla Canton, Bosnia and Herzegovina (sample included about 10% of the student population, i.e. 1645 student). Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…This Algorithm is a combination of several tree predictors, or it can be called a decision tree, where each tree depends on a random vector value sampled freely and evenly on all trees in the forest [31]. The prediction results from the Random Forest get the most results from each decision tree [32].…”
Section: ) Support Vector Regression (Svr): Svr Is a Development Of T...mentioning
confidence: 99%
“…This Algorithm is a combination of several tree predictors, or it can be called a decision tree, where each tree depends on a random vector value sampled freely and evenly on all trees in the forest [31]. The prediction results from the Random Forest get the most results from each decision tree [32].…”
Section: ) Support Vector Regression (Svr): Svr Is a Development Of T...mentioning
confidence: 99%
“…In a related study to categorize student performance into distinct classes and stages, Bharti [6] also revealed that Nave Bayes delivers the best Specificity when compared to the C.5 decision tree. According to Osmanbegovi and Sulji [7], when predicting True Negative values, the Nave Bayes algorithm outperforms MLP and C.45.…”
Section: Related Workmentioning
confidence: 99%
“…According to Ashari, Paryudi and Tjoa [18], Naïve Bayes is the best algorithm for classifying students' performance based on Precision, Recall, Fmeasure, Accuracy, and AUC as it could outperform Decision Tree and k-Nearest Neighbor. Also, Osmanbegovi and Suljic [7] reported that the Naïve Bayes algorithm is more efficient when compared with MLP and C.45 in predicting True Negative values.…”
Section: Critical Analysis Of Classification Algorithmsmentioning
confidence: 99%